2022
DOI: 10.1177/00037028221092474
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Near-Infrared Noninvasive Glucose Measurement and Detection in Humans

Abstract: In optical noninvasive glucose detection, how to detect the glucose-caused signals from the constant human variations and disturbed probing conditions is always the biggest challenge. Developing effective measurement strategies is essential to realize the detection. A NIR spectroscopy-based strategy is studied to effectively solve the in vivo measurement issues, obtaining clean blood glucose-caused signals. Two solutions composing our strategy are applied to the NIR spectroscopy-based measurement system to acq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 34 publications
(75 reference statements)
0
3
0
Order By: Relevance
“…The absorption coefficient, scattering coefficient, and refractive index of the skin layers (as shown in Figure 2(a) and 2(b)) were taken from reference 12. Assuming anisotropy factors is 0.9 for all skin layer 13 . Based on the assumptions stated in section 2.…”
Section: Monte-carlo Simulationmentioning
confidence: 99%
“…The absorption coefficient, scattering coefficient, and refractive index of the skin layers (as shown in Figure 2(a) and 2(b)) were taken from reference 12. Assuming anisotropy factors is 0.9 for all skin layer 13 . Based on the assumptions stated in section 2.…”
Section: Monte-carlo Simulationmentioning
confidence: 99%
“…4.1.5. Near-Infrared (NIR) Spectroscopy Considered one of the most effective techniques, NIR Spectroscopy shines light in the range of 750 nm to 2.5 µm onto the skin, such as the fingerprint, and the reflected light is measured [43][44][45][46][47], with accurate in vivo measurements demonstrated at 1550 nm for this particular technique [48]. Glucose molecules can absorb light, resulting in changes in the intensity of the reflected light at specific wavelengths, which are used to estimate the glucose concentration.…”
Section: Spectroscopymentioning
confidence: 99%
“…The strongest NIR absorption band from water in the NIR biological window is the O-H bond stretch at 1400-1450 nm [43], however water absorption is then at a local minimum in the region of the -CH overtone in glucose around 1688 nm, which means that this band offers promising potential for glucose quantification. NIR glucose sensing studies have been reported on glucose solutions [44][45][46], tissue phantoms [47,48] and human subjects [49,50]. Several different NIR optical variations have been reported, including photoplethysmography [51] and the use of lasers as light sources [52,53]; and the choice of optical components for infrared spectroscopy experiments is important.…”
Section: Introductionmentioning
confidence: 99%